Stakeholder Analysis in Urban Development in The Case of Sawankhalok City - Wijitporn, Thanawin; Tansukanun, Pranom (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This study is a significant part of an action research ‘In Searching for Appropriate Public Participation in the Medium Size Old City Planning Process in the Case of Sawankhalok City.’ It discusses conducting stakeholder analysis for understanding of the roles, powers, interest levels, and the relations between groups of stakeholders, in the Sawankhalok City Development Participation Project supported by the Community Organizations Development Institute in Thailand. This research classifies three key groups of the stakeholders as: governmental offices, private sector, and civil sector. One of the governmental offices, the Sawankhalok Town Municipality Comment: Is this the full title of the governmental office?], has the major role in the city’s development. It has the highest power to control the city’s development direction, as well as the greatest interests and influence in the city’s development. This research also found out that in the civil sector, both non-profit organisations and the people of Sawankhalok, have low levels of participation in the city development process. The study suggests that to create sustainable city development, an appropriate level of participation should be made available by enhancing the power and interest level of those in the non-governmental sector. Two suggestions are presented for short-term and long-term procedures. The short-term procedure is to encourage an atmosphere of city development participation by transforming the local government’s role responsibility from being the main player to being a supporter. Such a change can provide more opportunities and encourage increased levels of interest in participation from the civil sector. After the transformation gradually changes and becomes a concrete value of the city development process, then the long–term strategy will be developed to empower the stakeholder’s roles, their power, and their interests to the level of equality and equity. That implementation among all sectors can accordingly facilitate a level of city development co–creation that can raise the city development direction to that of a liveable and sustainable city.